Allylic oxidation of olefins with a manganese-based metal–organic framework. Issue 13 (5th June 2019) - Chen, Jingwen; Chen, Minda; Zhang, Biying; Nie, Renfeng; Huang, Ao; Goh, Tian Wei; Volkov, Alexander; Zhang, Zhiguo; Ren, Qilong; Huang, Wenyu
Abstract : Manganese-based CPF-5 as a highly efficient catalyst for the selective aerobic oxidation of cyclohexene to cyclohexenone under mild conditions. Abstract : Selective oxidation of olefins to α, β-unsaturated ketones under mild reaction conditions has attracted considerable interest, since α, β-unsaturated ketones can serve as synthetic precursors for various downstream chemical products. The major inherent challenges with this chemical oxidation are chemo- and regio-selectivity as well as environmental concerns, i.e. catalyst recycle, safety and cost. Using atmospheric oxygen as an environmentally friendly oxidant, we found that a metal–organic framework (MOF) constructed with Mn and a tetrazolate ligand (CPF-5) showed good activity and selectivity for the allylic oxidation of olefins to α, β-unsaturated ketones. Under the optimized conditions, we could achieve 98% conversion of cyclohexene and 87% selectivity toward cyclohexanone. The combination of a substoichiometric amount of TBHP ( tert -butylhydroperoxide) and oxygen not only provides a cost effective oxidation system but significantly enhances the selectivity to α, β-unsaturated ketones, outperforming most reported oxidation methods. This catalytic system is heterogeneous in nature, and CPF-5 could be reused at least five times without a significant decrease in its catalytic activity and selectivity.